RESEARCH OF PROCESSES ON FORMATION AND TRIBOTECHNICAL PROPERTIES OF WEAR-RESISTANT COMPOSITE GAS THERMAL COATINGS BEING DISPERSIVELY STRENGTHENED BY SYNTHETIC DIAMONDS AND ELECTRO-CORUNDUM - O. S. Kobjakov; N. V. Spiridonov (Наука и техника)
Formation processes, tribotechnical and wear-resistant properties of composite gas thermal coatings being dispersively strengthened by synthetic diamonds and electro-corundum are investigated in the paper.